Miejsca i tożsamość : Teatr lokalny na Dolnym Śląsku - Gołaczyńska, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Sites and Identity. Local Theatre in Lower Silesia is devoted to contemporary live performances, television theatre and paratheatrical actions exploring local themes. The objective of the book is to analyse the phenomenon of regional theatre that emerged in the late 20th and early 21st century. The analysis covers artistic and social projects the authors of which focus on presenting urban spaces and Lower Silesia as a “little homeland” as well as presenting the stories of its inhabitants. At the same time it demonstrates both the specificity and the universal nature of this trend. In the introduction I show several examples of post-war Polish “theatre of one’s site” from outside Lower Silesia. The book comprises three chapters and a conclusion; the main part is Chapter III. It is preceded by reflections on the evolution of the regional identity of people living in Lower Silesia (Chapter I) — from the post-war self-awareness through changes in the 1970s to the emergence of a new identity of civil society after 1989. Social changes are to some extent reflected in the evolution of local theatre. I discuss theatre in Lower Silesia and paratheatre from 1945–1989 in Chapter II, taking into account occasional performances and propaganda performances from the 1940s and 1950s, ideas from the 1970s, the exceptional — for its time action organised by Akademia Ruchu [Movement Academy] and entitled Dom III [House III] as well as Wrocław’s unique paratheatre, i.e. Pomarańczowa Alternatywa [Orange Alternative]. Chapter III deals with local performances and theatrical projects in Lower Silesia from 1989 until the end of 2010, from both institutional theatre and independent theatre, as well as television theatre. I take into account performances which are shown regionally and, at the same time, tackle local themes (they concern Lower Silesian places, people or objects). My interest focuses mainly on the choice of a “found” theatrical place or stage space as well as the space presented, created by the authors, and the relations between them. The question of choosing and transforming a site and its surroundings, which are very concrete in the theatre, also becomes crucial to the identity of the artists and spectators. Chapters I and III explain Lower Silesians’ special attitude to the place in which they live and to the space in which they create. In the conclusion I sum up the preceding reflections, defining the authors’ strategies with regard to the past and the present, strategies they use in their work, as well as the choices associated with specific theatrical places.
Keywords: teatr polski; happening; performance; regionalizm; tożsamość społeczna; tożsamość regionalna